NLRP3 Inflammasome Formation and Activation in Nonalcoholic Steatohepatitis: Therapeutic Target for Antimetabolic Syndrome Remedy FTZ. (22nd July 2018) - Chen, Yu; He, Xingxiang; Yuan, Xinxu; Hong, Jinni; Bhat, Owais; Li, Guangbi; Li, Pin-Lan; Guo, Jiao
Abstract : The Nod-like receptor protein 3 (NLRP3) inflammasome activation not only serves as an intracellular machinery triggering inflammation but also produces uncanonical effects beyond inflammation such as changing cell metabolism and increasing cell membrane permeability. The present study was designed to test whether this NLRP3 inflammasome activation contributes to the "two-hit" injury during nonalcoholic steatohepatitis (NASH) and whether it can be a therapeutic target for the action of Fufang Zhenzhu Tiaozhi (FTZ), a widely used herbal remedy for hyperlipidemia and metabolic syndrome in China. We first demonstrated that NLRP3 inflammasome formation and activation as well as lipid deposition occurred in the liver of mice on the high-fat diet (HFD), as shown by increased NLRP3 aggregation, enhanced production of IL-1 β and high mobility group box 1 (HMGB1), and remarkable lipid deposition in liver cells. FTZ extracts not only significantly reduced the NLRP3 inflammasome formation and activation but also attenuated the liver steatosis and fibrogenic phenotype changed. In in vitro studies, palmitic acid (PA) was found to increase colocalization of NLRP3 components and enhanced caspase-1 activity in hepatic stellate cells (HSCs), indicating enhanced formation and activation of NLRP3 inflammasomes by PA. PA also increased lipid deposition. Nlrp3 siRNA can reverse this effect by silencing the NLRP3 inflammasome and both with FTZ. In FTZ-treated cells, not only inflammasome formation and activation was substantially attenuated but also lipid deposition in HSCs was blocked. This inhibition of FTZ on lipid deposition was similar to the effects of glycyrrhizin, an HMGB1 inhibitor. Mechanistically, stimulated membrane raft redox signaling platform formation and increased O2 − production by PA to activate NLRP3 inflammasomes in HSCs was blocked by FTZ treatment. It is concluded that FTZ extracts inhibit NASH by its action on both inflammatory response and liver lipid metabolism associated with NLRP3 inflammasome formation and activation.